ANALISIS IMPLEMENTASI PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN MATEMATIKA MATERI BANGUN DATAR : STUDI KASUS PADA SISWA KELAS II SEKOLAH DASAR - Nurjannah; Kamid; Zahyuni, Violita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Contextual Teaching and Learning (CTL) approach in mathematics learning on plane geometry material for second grade elementary school students and to describe students’ understanding after the implementation of the approach. The background of this research is the low understanding of students toward plane geometry concepts, where more than 60% of students had difficulty recognizing and distinguishing basic shapes such as squares, rectangles, and triangles. The study employed a descriptive qualitative research design. The research was conducted at SDN 19/1 Muara Tembesi with the subjects consisting of second grade students and the mathematics teacher. Data were collected through observation, interviews, and documentation. The data were analyzed using descriptive analysis to describe the process of implementing the contextual approach and its impact on students’ conceptual understanding. The findings show that the implementation of the CTL approach can create more meaningful learning by linking mathematical concepts with students’ real-life experiences. Through contextual activities such as observing objects in the surrounding environment, asking questions, group discussions, and reflection, students became more active and engaged in the learning process. As a result, students were able to better recognize the characteristics of plane figures and understand the concepts more concretely. Therefore, the contextual approach can be considered an effective strategy to support mathematics learning in elementary school, especially in helping students understand abstract concepts through real-life contexts.